Ambipolar field role in formation of electron distribution function in gas discharge plasma. Issue 1 (December 2017) - Yuan, Chengxun; Bogdanov, E.; Kudryavtsev, A.; Rabadanov, K.; Zhou, Zhongxiang
Abstract It is shown that the local approximation for electron distribution function (EDF) determination at plasma periphery, where the ambipolar field is dominant, is not applicable even at high pressures when the characteristic plasma size exceeds the energy relaxation length of the electronsR  > λ ε . Therefore, consistent results can be obtained only when solving the complete kinetic equation in both energy and spatial variables (i.e. it is necessary to solve nonlocal kinetic equation).